Financial literacy and retirement planning: New evidence from the Rand American Life Panel - Annamaria Lusardi; Olivia S. Mitchell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2007)
The present paper introduces a new dataset, the Rand American Life Panel (ALP), which offers several appealing features for an analysis of financial literacy and retirement planning. It allows us to evaluate financial knowledge during workers' prime earning years when they are making key financial decisions, and it offers detailed financial literacy and retirement planning questions, permitting a finer assessment of respondents' financial literacy than heretofore feasible. We can also compare respondents' self-assessed financial knowledge levels with objective measures of financial literacy, and most valuably, we can investigate prior financial training which permits us to identify key causal links. By every measure, and in every sample we examine, financial literacy proves to be a key determinant of retirement planning. We also find that respondent literacy is higher when they were exposed to economics in school and to company-based financial education programs.
urn:nbn:de:hebis:30-51363
Keywords: D91; 330; Financial Literacy; Retirement Planning; Financial Education; Alterssicherung; Kapitalanlage; Wissen; USA